The Effectiveness of Fisherman Community Empowerment Programs Through Fisheries Actor Business Cards - Gazali Gazali; Sudiarti Dewi Kurra; Dewi Sulfa Saguni; Muhammad Arifai; Abd. Rahman Yus (Program Pascasarjana Universitas Negeri Makassar, 2024)
This study aims to determine the effectiveness of the Fisherman Community Empowerment Program through Fisheries Actor Business Cards in Landolia Village, Ranteangin District, North Kolaka Regency. This type of research was conducted with qualitative research methods, data collected from primary data and secondary data. Primary data sourced from interviews with informants totaling 11 people and from observations. As for secondary data by collecting data through literature studies and other supporting literature. The data analysis technique used is qualitative data analysis using data collection, data reduction, data presentation, and drawing conclusions put forward by Miles and Hubberman. Based on the results of the study indicate that the effectiveness of the Fisher Community Empowerment Program through the Fisheries Actor Business Card (KUSUKA) Landolia Village, Ranteangin District, North Kolaka Regency through 4 indicators to measure the effectiveness of the program, namely: 1) the accuracy of the program targets, the effectiveness of the Fisherman Community Empowerment Program through the Kusuka Card in the village. Landolia, Ranteangin District, North Kolaka Regency has not been effective because the target accuracy indicator has not been effective because the target achievement is less than all program targets, 2) Program socialization on program socialization indicators in the fishermen community empowerment program through Kusuka is still not effective because of the low interest of the community to participate in socialization. 3) program objectives, with the Kusuka program for fishermen groups in Landolia Village, it is said to be quite effective because it really helps the community in meeting their daily needs. 4) Program Monitoring Based on the explanation above, the authors conducted further searches and saw data on the members of the fishing group who received the assistance provided through the Kusuka program, which is still not considered effective because not all members of the fishermen use the assistance programs properly.